Trends in HIV and HCV Risk Behaviors and Prevalent Infection Among People Who Inject Drugs in New York City, 2005–2012. (1st July 2017) - Neaigus, Alan; Reilly, Kathleen H.; Jenness, Samuel M.; Hagan, Holly; Wendel, Travis; Gelpi-Acosta, Camila; Marshall, David M.
Abstract : Background: We assess trends in HIV and hepatitis C virus (HCV) risk behaviors and prevalent infection among people who inject drugs (PWID) in New York City (NYC). Methods: PWID in NYC were sampled using respondent-driven sampling in 2005, 2009, and 2012 (serial cross sections) for the Centers for Disease Control and Prevention–sponsored National HIV Behavioral Surveillance study. Participants were interviewed about their current (⩽12 months) risk behaviors and tested for HIV and HCV. The crude and adjusted risk ratio (RR) and 95% confidence interval (95% CI) for linear time trends were estimated using generalized estimating equations regression with a modified Poisson model. Results: The sample comprised 500, 514, and 525 participants in 2005, 2009, and 2012, respectively. Significant ( P < 0.05) linear trends in risk behaviors included a decline in unsafe syringe sources (60.8%, 31.3%, 46.7%; RR = 0.86, 95% CI: 0.81 to 0.92), an increase in all syringes from syringe exchanges or pharmacies (35.4%, 67.5%, 50.3%; RR = 1.15, 95% CI: 1.09 to 1.22), and an increase in condomless vaginal or anal sex (53.6%, 71.2%, 70.3%; RR = 1.14, 95% CI: 1.09 to 1.19). Receptive syringe sharing (21.4%, 27.0%, 25.1%), sharing drug preparation equipment (45.4%, 43.4%, 46.7%), and having ≥2 sex partners (51.2%, 44.0%, 50.7%) were stable. Although HIV seroprevalence declined (18.1%, 12.5%, 12.2%), HCV seroprevalence was high (68.2%, 75.8%, 67.1%). In multivariate analysis, adjusting for sample characteristics significantly associated with time, linear time trends remained significant, and the decline in HIV seroprevalence gained significance (adjusted RR = 0.76, 95% CI: 0.64 to 0.91, P = 0.003). Conclusions: This trend analysis suggests declining HIV prevalence among NYC PWID. However, HCV seroprevalence was high and risk behaviors were considerable. Longitudinal surveillance of HIV and HCV risk behaviors and infections is needed to monitor trends and for ongoing data-informed prevention among PWID.